Kajian Penerapan Arsitektur Hijau pada Perancangan Sekolah Alam - Karina Az-Zahra Marsaf; Hilma Tamiami Fachrudin (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The success of education for children is determined by education carried out from an early age. The purpose of education in general is to provide an environment that allows students to develop their talents and abilities optimally. Because every child has different abilities and talents. School is one source of children's learning, unfortunately, most schools today focus more on academic aspects and evaluation, while outdoor learning by utilizing nature as a learning medium can help explore children's hidden talents and potentials. The environment has an important role in children's growth and development, because children will first learn and understand various things through interaction with their environment. In this case, the environment becomes a source of learning that greatly influences the physical, skill, social, cultural, emotional, and intellectual development of children